Implementasi Kebijakan Merdeka Belajar Kampus Merdeka Melalui Program Magang dan Studi Independen Bersertifikat (MSIB) di Fakultas Pertanian UPN “Veteran” Jawa Timur - Effendy, Amelia Diva; Hertati, Diana (Jayapangus Press, 2024)
Around 12% of unemployment in Indonesia is dominated by Diploma and Bachelor graduates. This is because there is no link and match. Therefore, in 2020 the Ministry of Education and Culture released the Independent Campus Learning (MBKM) policy. The aim of this research is to determine the implementation of the MBKM Policy through the MSIB Program in Certified Internship Activities at the Faculty of Agriculture, UPN